New methods for the construction of C-18F bonds - Stenhagen, I (2014)
The main electrophilic source used in radiolabelling is [18F]F2, which is highly reactive, toxic and requires specialist equipment for safe handling. The Gouverneur group has initiated a research programme focused on the preparation of new stable and easy-to-handle N-18F reagents. In the development of [18F]radiolabelling reactions it would be extremely valuable to develop a library of selective N-18F reagents possessing reactivity tailored to the desired chemical transformation. The aim of this thesis is to further assess the scope of electrophilic N- 18F reagents in new transformations for the construction of C-18F bonds.